2007
DOI: 10.1111/j.1365-4632.2007.03150.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoepitheliomatous hyperplasia – an unusual reaction following tattoo: report of a case and review of the literature

Abstract: A 59-year-old woman presented with an itchy and uncomfortable raised lesion at a tattoo site (Fig. 1) on the lateral aspect of the left leg, just above the ankle. The tattoo had been placed 2 years before her presentation and the tattoo site was sun exposed. Immediately after she had the tattoo, she noticed redness of the skin. After a week, a pruritic and red scaly nodule developed that continued to gradually enlarge until her presentation. The patient had tried topical vitamin A and D ointment with no relief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 14 publications
0
34
0
2
Order By: Relevance
“…It may be of interest to note that different patterns may occur simultaneously on different tattoos of a single patient. [4] The occurrence of PH has rarely been reported in this setting and only within red [5][6][7][8] or purple [9] areas of tattoos to date. PH refers to a benign irregular hyperplasia of the epidermis that can also involve follicular infundibulum and acrosyringium.…”
Section: Casementioning
confidence: 99%
“…It may be of interest to note that different patterns may occur simultaneously on different tattoos of a single patient. [4] The occurrence of PH has rarely been reported in this setting and only within red [5][6][7][8] or purple [9] areas of tattoos to date. PH refers to a benign irregular hyperplasia of the epidermis that can also involve follicular infundibulum and acrosyringium.…”
Section: Casementioning
confidence: 99%
“…Goldberg in 1959 (18), as multiple verrucous papules forming exclusively in the area of red tattoo ink. A few more cases of pseudoepitheliomatous hyperplasia were described later, where the authors reported various ways of adverse reaction development from the moment of ink application, lasting from four days to 12 months, with the process localization on forearms, back, and lower limbs (9,10,(19)(20)(21). The trigger effect of solar radiation on pseudoepitheliomatous hyperplasia development was observed (20,22,23).…”
Section: Introductionmentioning
confidence: 99%
“…A few more cases of pseudoepitheliomatous hyperplasia were described later, where the authors reported various ways of adverse reaction development from the moment of ink application, lasting from four days to 12 months, with the process localization on forearms, back, and lower limbs (9,10,(19)(20)(21). The trigger effect of solar radiation on pseudoepitheliomatous hyperplasia development was observed (20,22,23). Histopathological examination of the skin biopsy sample taken from a lesion shows epidermal and infundibular hyperplasia, signs of epidermal vacuolization and dyskeratosis, lymphocytic and histiocytic dermal infi ltration with red pigment gra nules more rarely -local areas of dermoepidermal junction damage (9).…”
Section: Introductionmentioning
confidence: 99%
“…These features consent the differential diagnosis by squamous cell carcinoma. 3,4 In literature, there are few cases of PEH to tattoos, but it is very important that clinicians be aware of this possibility and of the possible development of cutaneous cancer in the site of tattoo.…”
mentioning
confidence: 98%